METODE PENDIDIKAN ANAK DALAM KISAH NABI IBRAHIM DAN NABI ISMAIL MENURUT Q.S. ASH-SHAFFAT 102 - Zaenussalam, Ihsan; Herlina, N. Hani; Daryaman, Daryaman (Jurnal Penelitian Pendidikan Islam, 2015)
This research was conducted to explore and analyze data about the method of children's education in the story of Prophet Ibrahim a.s. and Prophet Ismail a.s. in Q.S. Ash-Shaffat verse 102. This study yields the following conclusions: 1) Based on the interpretation of Ibn Kathir, Al-Maraghi and M. Quraish Shihab that Q.S. Ash-Shaffat verse 102 is understood as the interaction of the education of Prophet Ibrahim and Prophet Ismail about the command to slaughter (the Shari'a to sacrifice) obtained from God through intuition. As an effort to socialize the knowledge of education obtained by Prophet Ibrahim from the first source of Allah, it was formulated in a dialogical-democratic method. 2) Dialogue-democratic methods describe two-way educational interactions between educators and students. The effectiveness of this method conditions education in a democratic manner, because it empowers students' potential rationally and emotionally. Educational implementation uses these methods in schools by providing opportunities for students to speak up. The implementation of dialogical-democratic methods in the family environment requires parents to give more recognition to children, hear their opinions, and communicate and provide freedom of choice to children related to their future lives.